Perspectives on the security of Singapore : the first 50 years - Desker, Barry; Ang, Cheng Guan (New Jersey : World Scientific, 2016)
'[This book] explores the security of Singapore in the last 50 years and its possible trajectories into the future. This volume brings together the diverse perspectives of a team of academics with different expertise, ranging from history to political science to security studies with a common interest in Singapore. The book is further boosted by the recollections of key civil servants involved with foreign affairs and defence, such as S R Nathan, Peter Ho, Bilahari Kausikan and Philip Yeo'--
Includes bibliographical references.
Keywords: National security -- Singapore